Digital transformation of agencies for students' part time jobs in the Republic of Croatia - Nidogon Višnjić, Sonja (Array, 2021)
Digital transformation (DT) of agencies for students`part time jobs in the Republic of Croatia (RC) began to be mentioned through the adoption of the Act of student activities (Act). The work of students in the Republic of Croatia is regulated by the Act [1], which provides the legal basis for the DT system of mediation in employment. The Act and the Ordinance oblige the mediator to keep all records in electronic form and define the possibility of issuing student contracts in electronic form, but up to now this form of contract has not been experienced in practice [1], [2]. The distinction between digitization and DT in part led to the fact that the electronic student contract currently implies the issuance of an online student contract, which was not signed by an advanced electronic signature. Changes in business caused by COVID-19 contributed to greater utilization of existing online contracts and pointed to inconsistencies in the work of intermediaries. The aim of this paper is to present, based on a literature review and analysis of the existing situation through the case study, the conceptual model of the DT system for mediation in employment and to test the digital maturity of the current system. The scientific contribution of the paper is in presenting a model that can be implemented in the daily practice of all students employment agencies, while the social contribution is reflected in the attempts of DT public institutions that should be used as an example to the private sector.